"Treatment is not yet necessary": delays in seeking access to HIV treatment in Uganda and Zimbabwe. Issue 3 (28th September 2018) - Kawuma, Rachel; Seeley, Janet; Mupambireyi, Zivai; Cowan, Frances; Bernays, Sarah; ,
Abstract : We examined the logic that individuals use to account for delaying HIV testing and/or initiating HIV treatment. Our qualitative study, situated within the REALITY trial (R eduction ofEA rly mortaLITY in HIV infected adults and children starting antiretroviral therapy), was conducted in Uganda and Zimbabwe in 2015. Forty-eight participants (different age groups, sex and viral load/WHO disease stage) were included. Each participant had 2 interviews (1 after 4 weeks of participation in the trial the other after 12 weeks). If a person could manage presenting symptoms, they felt they had "more time" before starting antiretroviral therapy (ART). Their reluctance to have an HIV test (despite deteriorating health) arose from a belief that they were not "sick", that treatment was "not yet necessary". People in our study did not consider themselves as presenting "late", and treatment was not considered urgent as long as they considered their health to be "good enough".